INTERAKSI BAP (Benzil Amino Purin) DAN IAA (Indole Acetic Acid) PADA EKSPLAN ANTHURIUM (Anthurium sp) DALAM KULTUR JARINGAN - Selvia Sutriana; Hasan Basri Jumin; Hercules Gultom (DINAMIKA PERTANIAN, 2012)
The aim of this research was to get a combination of BAP and IAA concentration which give the best effect on anthurium explants in tissue culture. The research was carried out at Biotechnology Laboratory of Faculty of Agriculture Riau Islamic University Pekanbaru during four months, starting from august to November 2009. The method used was completely randomized design with two factors. The first factor is given BAP and the second one was given IAA. The observed parameters were explants survive percentage, bud emerge age, root emerge age, bud number, root number, and bud height. The observation data was analyzed statistically and advanced test using BNJ at a 5% significant level. The results show that the combined BAP and IAA application had interactionally an effect on root emerge age, bud number, root number, and bud height. Individually, BAP application had an effect on bud emerge age, root emerge age, bud number, root number, and bud height with without BAP had a significant effect. While, IAA application affected significantly on bud emerge age, root emerge age, bud number, root number, and bud height.